Efektivitas Sistem Daring terhadap Kualitas Daya Serap Pembelajaran Peserta Didik - Irawan, Vaesol Wahyu Eka (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
The Covid-19 pandemic has changed the implementation of learning into an online system, which is to fulfill one of the educational principles that prioritizes the safety of all involved in the education process and the general public. This situation forces the application of the e-learning learning model which in its familiar terms with the online name becomes real to be fully applied. With the descriptive evaluative step, it is hoped that it will become one of the informative treasures in the policy of implementing this system better. If it is developed, it is possible that it will become a system that will continue to be maintained even though the pandemic storm has passed. However, online education cannot be used as a learning model that is continuously carried out, because it reduces the psychomotor affective side which is the goal of Indonesian national education